Risk Control of Construction Worker Hazards at Heights - Putri, Risa Anggita; Rasyad, Mohamad Hanif; Fitriana, Della Rizky; Mei, Aura Sasi; Bate, Maria Estefania; Abdullah, Nabila; Goldstein, Simon (Journal of Safety Education, 2024)
An occupational accident is an unexpected and unplanned occurrence, including acts of violence, arising out of or in connection with work, which results in one or more workers incurring a personal injury, disease, or death. Based on data from the ILO, every year, 2.78 million workers die due to occupational accidents and occupational diseases, of which 2.4 million (86.3%) are related to both occupational accidents and diseases. In comparison, the other 380,000 workers (13.7%) are due to occupational diseases only. The purpose of this study is to determine the risk control of hazards in high-altitude workers. The research method used is descriptive observational research that focuses on events that occur and is described in the form of a narrative. The results of this study indicate that there are still many workers who have not implemented hazard risk control at height and still do not use PPE when working at height. Controls that can be carried out are control through administrative work procedures, work safety analysis, making PPE completeness standards in the project area that are more tightened, and control of using PPE at height.